Penerapan Metode Problem Based Learning dalam Menciptakan Suasana PAKEM untuk Meningkatkan Prestasi Belajar Pendidikan Agama Hindu dan Budi Pekerti - Ni Made Ayu Astiti (Jayapangus Press, 2019)
The phenomena faced in Hinduism and Budi's education are still found in cases of low interest and student learning achievement Based on these problems, one of the learning methods that can be used to attract students' attention and to create a learning atmosphere that is in accordance with the PAKEM climate (Learning Active, Creative, Effective and Enjoyable) is a method of Problem Based Learning. This paper discusses (1) Cooperative Learning (2) Problem Based Learning Methods (3) Steps in Problem Based Learning Learning Methods.